(untitled) (Journal of Oriental Studies, 2022)
Akhmet Baitursynov, who had an important place in Kazakh intellectual and educational life at the beginning of the 20th century, focused his studies in the field of education and was influential in the restructuring of the Kazakh education system. In addition, Baitursynov, who made efforts to make Kazakh a writing language, studied the alphabet for illiterate people in this direction, prepared textbooks and wrote articles about education. Baytursınulı, who also wrote books on the grammar of Kazakh, was also interested in the topic of Kazakh term derivation. Baitursynov, who also participated in the Turcology Congress held in Baku in 1926 and gave his opinion on the alphabet, has an important place in Kazakh Turcology. The fact that he created a new alphabet by changing the Arabic alphabet according to the sound characteristics of Kazakh is considered to be his greatest service to Kazakh Turkology. The Baitursynov alphabet spread from 1912 onwards, began to be used in madrasas and Kazakh-Russian schools after 1913, and in 1929 it fell out of use due to the fact that Kazakh was written in the Latin alphabet. Today, this alphabet, which was forgotten in Kazakhstan, is still used by Kazakhs in East Turkestan. The studies on the place of Akhmet Baitursynov in Turkology can be taken back to 1919. Although the first studies were conducted by Russian scientists, important studies on Baitursynov were also revealed in Kazakhstan and a discipline was established. Important studies have been carried out on Akhmet Baitursynov in Turkey as well. It is among the purposes of writing this article to introduce studies on Baitursynov in Turkey.